Academic Governance in Higher Education Institutions - Mohammad Nashief; Azza Said Al –Sharji (Route Educational & Social Science Journal, 2024)
One of the outcomes of the scientific and knowledge revolution and Information and Communication Technology witnessed in the world today is the civilizational openness, which led to facing a major challenge to most countries of the world. This has been further complicated by rapid and frequent dynamic transformation and increasing growth of the requirements of human needs satisfaction. Therefore, the establishment of mechanisms and strategies to coexist with this civilizational openness with its various aspects, the social aspect of which is one of the most prominent aspects, has become one of the most urgent human needs at the present time. In view of the foundations of social systems, we find that the educational system comes at the forefront of such systems because it is the basis of building all generations; the success or failure of this system is reflected on various components of the society. Therefore, this system shall be the major concern of those in charge to know its progress and weakness and to rectify the deviation if any (Almuqemia, 2014). All organizations ensure to carry out administrative reform programs as being an important step for the development of their economic and social development, as well as help to consolidate and establish the general policies of the state and raise the quality of effectiveness of government programs and its continuous support to public and private institutions. Universities are currently in the age of knowledge and looking for more efficiency, which make the Higher Education Department requires the adoption of modern policies to shift from traditional model to more developed methods such as governance. Moreover, attention given to the issue of governance, especially in the governance of universities in the past few years, has increased for some considerations, the most important of which is the fact that governance constitutes the framed organizing to determine the objectives of the higher education institutions and to manage its resources and components in accordance with the rules of transparency, participation and accountability in order to improve education, ability to face the technological challenges, the increasing number of public and private higher education institutions and having higher requirements of labor market (Al Alfi, 2016: 11).